MARKETING POLITIK DI MEDIA MASSA DALAM PEMILU 2009 - Gun Gun Heryanto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
The phenomena of general election in 2009 shows that political marketing is an important part of winning thecompetition. This marketing approach has been transparently used since 1999 and continued to 2004. However, its more intensive usecould be seen in the last general election in 2009. It was probably the era of an image industry which force an individual and a party toconstruct their best image in mass media. The more democracy following the fall of New Order enables all political power to competefairly. This condition is in line with the wind of press independence which grows as a developing industry. In relation to the generalelection, mass media can be synergetic with political agents or the candidates. For the media, politics is considered as a product orservice which has a high economical value; and for the politicians, mass media is a means of political communication to raise theirpopularity